ENHANCING STUDENTS' TOEFL SKILLS THROUGH STRATEGY-BASED TRAINING - Desi Herayana; Baiq Annisa Shallaita; Atri Dewi Aziz; Eka Fitriana (Jurnal Pepadu, 2026)
This Community Service Program (PKM) aims to increase awareness and understanding of students in the region regarding the importance of English and TOEFL test in facing global competition and to provide concrete solutions to students' difficulties in preparing for TOEFL test. This program is conducted through a series of activities, including:  Pre-test, training on TOEFL material coverage and strategies (Listening, SWE, and Reading Comprehension), and post-test. The target group for this program is 29 students from grades 10 to 12 at SMAN 1 Praya Barat Daya. The program is guided by the PKM Team from the English Education Study Program, University of Mataram. The program is held at SMAN 1 Praya Barat Daya as a partner. The results of the pre-test and post-test indicate the increase of student understanding of the TOEFL test and improved skills in answering TOEFL tests